Aetiology of superficial fungal infections of the foot in urban outpatients in mainland China: A multicentre, prospective case study. Issue 11 (9th September 2020) - Yu, Jin; Liu, Wei‐Da; Tong, Zhong‐Sheng; Yu, Nan; Cao, Cun‐Wei; Zhou, Xun; Li, Yu‐Zhen; Zhang, Yu; Li, Fu‐Qiu; Zhang, Jun‐Min; Zhu, Min; Yang, Lian‐Juan; et al.
Summary: Background: In China, the prevalence of superficial fungal infections of the foot is high and recurrence is common. However, a prospective, large‐scale and multicentre study on the aetiology of superficial fungal infections of the foot is still lacking. Objectives: To study the epidemiology of aetiological agents of superficial fungal infections of the foot in urban outpatients in mainland China, as well as to understand the aetiology features of the pathogenic agent. Methods: The study was designed as a multicentre, prospective epidemiological survey. A total of 1704 subjects were enrolled from seven geographical areas in mainland China. For each subject, one mycological sample and one bacterial sample were collected. KOH wet mount examination and culture were performed at local laboratories. The bacterial results were only reported in those with positive mycology. Further morphological identification and, if necessary, molecular biological identification were conducted in a central laboratory. Results: Of 1704 enrolled subjects, 1327 (77.9%) subjects had positive fungal culture results. The incidence of dermatophytes, yeasts and moulds was 90.1%, 8.1% and 1.1%, respectively. The most frequently isolated aetiological agent (fungus) was Trichophyton rubrum . Moccasin form was the most commonly reported clinical diagnosis of superficial fungal infections. The most frequently isolated bacterial genus in patients was Staphylococcus . Conclusion: This study prospectively investigated the clinical and mycological features of human dermatophytosis in mainland China. T rubrum was the most frequently isolated fungus, and moccasin form was the most commonly reported clinical diagnosis of superficial fungal infections.